Trastorno adaptativo y sus efectos psicosociales en una persona privada de libertad - Lema Holguin, Ronny Adrian (2019)
The present case study shows the adaptive disorder and psychosocial effects of a person deprived of liberty, in which a 19-year-old, single, male person is carried out, where his sentence is in process, but he is accuses with his ex-partner of involvement of drug microtrafficking the apprehension affected in the early hours of February 20, 2019 in the San Carlos parish of the city of Quevedo in the province of Los Ríos. In this study, an evaluation of the adaptive disorder and the psychological, social effects that are presented and will be presented in the prison context is reported, which interferes with the activities of the individual, to whom psychological tools are applied that help to obtain important information. that help establish a subsequent correct diagnosis establish a cognitive behavioral therapeutic scheme, reducing the important symptoms of adaptation disorder